Agricultural Drought and Its Potential Impacts: Enabling Decision-Support for Food Security in Vulnerable Regions - Orimoloye, Israel R. (Frontiers in Sustainable Food Systems, 2022)
Increasing demand for food and environmental stressors are some of the most challenging problems that human societies face today and these have encouraged new studies to examine drought impacts on food production. Seeking to discuss these important issues in the South African context, this study analysed the impacts of drought on food security in one of the country's largest commercial agricultural land (Free State Province). Earth observation and crop data were acquired from Application for Extracting and Exploring Analysis Ready Samples (AppEEARS) and GrainSA databases, respectively for years 2011/2012 to 2020/2021 over Free State Province. Two crops namely, maize and sorghum were obtained from the database and analysed accordingly to quantify drought impacts on the two crops. The result reveals that the years 2015 and 2018 were affected by extreme drought events (<10%) where the majority of the study area was impacted. Years 2011, 2016, 2018 and 2019 were severely affected by drought (>30%) and impacted the agricultural sector in the study area. Findings further revealed that maize production observed the lowest recorded in the year 2014 and 2015 with about 2236,00 and 1190,50 tons, respectively. More so, results further showed that sorghum production recorded the lowest production in years 2019, 2016 and 2015 with about 23, 600, 24, 640 and 24, 150 tons, in that order during the period of study. The results confirm the impacts of drought on maize and sorghum productions in the year 2015 and other years that recorded the lowest productions during drought years. This development might have impacted food security in the study area, and this outcome will enable decision-making bodies on food security to enhance improved strategy in vulnerable areas.